Pengelolaan Sarana Dan Prasarana di Sekolah Madrasah Aliyah Laboratorium UINSU - Hasyim Basid Siagian; Tengku Darmansah; Farras Fadhilah; Nurul Atika Hasibuan; Rizki Rahmadani Safitri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research examines the management of facilities and infrastructure at the Madrasah Aliyah Laboratory of UIN North Sumatra (UIN SU) using quantitative and qualitative approaches. The aim of the research is to identify the main obstacles in facility management and provide strategic recommendations for improvement. Through a quantitative survey, it was found that there were significant differences in perceptions between teachers and students regarding the condition of school facilities, with teachers tending to be more critical. Further analysis shows that planned and routine maintenance plays an important role in preventing further damage and reducing long-term repair costs. In addition, the level of student satisfaction with facilities and infrastructure varies by grade level, with students in higher grades showing lower levels of satisfaction. A qualitative approach through in-depth interviews revealed that budget constraints were the main obstacle in facility management. Based on these findings, several strategic recommendations were proposed, including increasing budgets and resources through collaboration with external parties, implementing continuous training programs for teachers and staff, improving communication with parents, and implementing information technology in facility management. It is hoped that the implementation of these recommendations can improve the quality of management of facilities and infrastructure, which will ultimately have a positive impact on the quality of education in this madrasa. This research makes an important contribution to the education management literature, especially in the context of madrasas in Indonesia, and becomes a reference for future research and practice.